Politics in South Asia: culture, rationality and conceptual flow - Wolf, Siegfried O.; Schöttli, Jivanta; Frommherz, Dominik; Fürstenberg, Kai; Gallenkamp, Marian; König, Lion; Pauli, Markus (Springer, 2015)
The book introduces central themes that have preoccupied the field of South Asian politics over the last few decades and identifies new, emerging areas of research. Presenting both general political theory and context-specific case studies, the collection draws attention to the methodological challenges of working on an area-specific theme and the importance of generating generalizable insights linked to theory. Hence it will be of interest for political scientists working on South Asian politics as well as on other non-Western societies. The collection represents an unusually broad survey of scholarship emerging from a range of leading academic centres in the field
Keywords: Aufsatzsammlung; Politik; Südasien